Thermal analysis of failed-batch palm oil by differential scanning calorimetry - Che Man, Y.B.; Swe, P.Z. (Springer-Verlag, 1995)
Thermal behavior of palm oil samples drawn from the batch crystallizers that failed during crystallization and of a control oil that was drawn from a batch that produced good crystallization were analyzed by differential scanning calorimetry under constant heating and cooling conditions. Four polymorphs-β'2, α, β'1, and β1-were observed, and their temperatures were tabulated. A rapid and sudden surge of heat demand was observed for samples from failed crystallizers. Less supercooling values were obtained from the control oil compared to the higher values for samples from failed crystallizers. In crystallization thermograms, a sharp high-temperature exotherm (high-T peak) and a broad low-temperature exotherm (low-T peak) were observed. Low-T peaks were found almost invariably stationary at -5.1 to -5.6°C, and high-T peaks varied depending on the saturation level of the oil. A new peak, sandwiched between the high-T and low-T peaks, was observed for the control oil.